Social Work as The Safety Net of the Albanian Society in Transition - Arlinda Ymeraj (Prizren Social Science Journal, 2018)
Social work has little tradition as an academic discipline or as a profession in Albania despite the high need for well-trained social workers. Social work in Albania had practically not existed in the past, neither before the WWII nor during socialist regime. It was the deep political and economic changes of the post socialist phase and the support of government and non-government stakeholders, like the Ministry of Labour, Social Affairs, Emigration and Ex- Persecuted People as well as the Grand Valley University, Michigan, which paved the way for the establishment from scratch of the Faculty of Social Work at the University of Tirana in 1992. Two other schools of Social Work were also established in two public universities, one at the University of Shkodra (2005) and another at the Elbasan University (2004).  The Albaniaâ€™s adherence to the Bologna Declaration brought a new reform, initiated in 2005, in which the Departments of Social Work were actively involved and played a critical role to adjust the curricula according to the EU standards.